Opportunities and Barriers to Using the QRIS Payment System for the Development of Culinary MSMEs in Sibolga City - Pratiwi, Putri Khairani; Yusrizal; Syarbaini, Ahmad Muhaisin B. (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
There will be many changes in various sectors throughout the industrial revolution 4.0, whether prepared or not. The business world is one that will be affected by this development. With the development of this technology, people cannot avoid the ease of carrying out financial transactions. In the Sibolga City area, especially Sibolga Square, the use of QRIS is still very minimal because MSMEs still do not know more about the use of QRIS. The aim of this research is to find out what are the opportunities and obstacles to using the QRIS payment system for the development of MSMEs in Sibolga Square. This research uses descriptive qualitative methods. The data source used is primary data, namely information sourced from interviews with MSME actors in Sibolga Square, while secondary data is data obtained through searching various references that are related or already available and collected by other parties. Based on the results of research that has been carried out, it can be concluded that QRIS makes it easier for MSMEs and consumers to carry out transactions, by using QR technology the payment process is faster and more efficient, reduces cashier queue times and speeds up customer turnaround. Meanwhile, the inhibiting factors are that MSME players do not yet understand how the QRIS system is used, then there are problems with an unstable internet network in carrying out transactions, as well as a merchant discount rate (MDR) fee of 0.07% which is applied to traders.